The genera Cryptaulax and Procerithium (Procerithiidae, Caenogastropoda) in the Early Jurassic of Patagonia, Argentina - Ferrari, Silvia Mariel (2012)
New species of Cryptaulax and Procerithium (Procerithiidae, Caenogastropoda) are reported from the Lower Jurassic (Pliensbachian-Toarcian) marine deposits of west-central Chubut province, Argentinean Patagonia. Three new species are described: Cryptaulax redelii, Procerithium (Rhabdocolpus) patagoniensis and Procerithium (Infacerithum) nodosum; and the diagnoses of Cryptaulax damboreneae Ferrari and Procerithium nulloi (Ferrari) are emended. The new fossils derive from the Mulanguiñeu and Osta Arena formations and expand the known diversity of the Procerithiidae, extending its palaeobioeographical distribution into the South American Jurassic.